2013
DOI: 10.1007/s00330-013-3010-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Crohn’s disease activity: Initial validation of a magnetic resonance enterography global score (MEGS) against faecal calprotectin

Abstract: • Magnetic resonance imaging is now widely used to assess Crohn's disease. • Existing MRI activity scores depend on local segmental endoscopic/histological reference standards. • Scores including assessment of disease extent/complications better demonstrate full disease burden. • This new global Crohn's disease burden score correlates with calprotectin and CRP. • The MRI enterography score of disease activity can complement existing clinical markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
83
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(99 citation statements)
references
References 36 publications
7
83
1
5
Order By: Relevance
“…For example, the CD activity score has been developed and validated against a histological standard of reference 28 and has recently been extended to provide a global MRI activity score (MRI enterography global score). 6 However, in previous work no significant correlation was found between the MRI enterography global score and HBI (r = 0.102, p = 0.40) in a cohort of 71 patients. 6 Additionally, Makanyanga et al 6 reported no correlation between a CD activity score and HBI (r = 0.045, p = 0.630).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…For example, the CD activity score has been developed and validated against a histological standard of reference 28 and has recently been extended to provide a global MRI activity score (MRI enterography global score). 6 However, in previous work no significant correlation was found between the MRI enterography global score and HBI (r = 0.102, p = 0.40) in a cohort of 71 patients. 6 Additionally, Makanyanga et al 6 reported no correlation between a CD activity score and HBI (r = 0.045, p = 0.630).…”
Section: Discussionmentioning
confidence: 95%
“…6 However, in previous work no significant correlation was found between the MRI enterography global score and HBI (r = 0.102, p = 0.40) in a cohort of 71 patients. 6 Additionally, Makanyanga et al 6 reported no correlation between a CD activity score and HBI (r = 0.045, p = 0.630). Indeed, HBI also correlates poorly with objective measures of inflammation such as faecal calprotectin (fCP).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…We did not include other indices in our analysis because of their inherent limitations such those derived based on expert opinion [15,16], or those derived using fecal calprotectin as reference standard [17] which has the caveat of a low sensitivity for detecting small bowel inflammation.…”
Section: Discussionmentioning
confidence: 99%